Clinical Correlates of the Anatomical Relationships of the Foramen Ovale: A Radioanatomical Study - Youssef, Ahmed; Carrau, Ricardo L.; Tantawy, Ahmed; Ibrahim, Ahmed Ali; Prevedello, Daniel M.; Otto, Bradley A.; Solares, Arturo C.; Filho, Leo F. S. Ditzel; Rompaey, Jason (Journal of Neurological Surgery Part B: Skull Base, 2014)
Introduction Endonasal endoscopic transpterygoid approaches are commonly used techniques to access the infratemporal fossa and parapharyngeal space. Important endoscopic endonasal landmarks for the poststyloid parapharyngeal space, hence the internal carotid artery, include the mandibular nerve at the level of foramen ovale and the lateral pterygoid plate. This study aims to define the anatomical relationships of the foramen ovale, establishing its distance to other important anatomical landmarks such as the pterygoid process and columella.Methods Distances between the foramen ovale, foramen rotundum, and fixed anatomical landmarks like the columella and pterygoid process were measured using computed tomography (CT) scans and cadaveric dissections of the pterygopalatine and infratemporal fossae.Results The mean distances from the foramen ovale to columella and from the foramen rotundum to columella were found to be 9.15 cm and 7.09 cm, respectively. Analysis of radiologic measurements detected no statistically significant differences between sides or gender.Conclusions The pterygoid plates and V3 are prominent landmarks of the endonasal endoscopic approach to the infratemporal fossa and poststyloid parapharyngeal space. A better understanding of the endoscopic anatomy of the infratemporal fossa and awareness of the approximate distances and geometry among anatomical landmarks facilitates a safe and complete resection of lesions arising or extending to these regions.
Keywords: infratemporal fossa; transpterygoid approach; foramen ovale; foramen rotundum; V2; V3